Ical di Mata Televisi dan Korban Lumpur Lapindo - Arzak, Miftahul (Jurnal ILMU KOMUNIKASI, 2014)
Abstract: This article aims to look at the audience reception of Ical’s candidacy as the President of Indonesia 2014-2019 period on television in Kludan RT 01 RW 02, Tanggulangin, Sidoarjo, East Java. This article is based on a research that analysed the reception of the villagers in Kludan as the victims of Lapindo mudflow in watching news on Ical’s candidacy on television while Ical is the owner of the industry that caused the mudflow. As a reception analysis, this research attempts to reinterpret and to analyze the audience reception and interpretation by using Stuart Hall’s encoding and decoding concept.Abstrak: Tulisan ini berniat mengetahui penerimaan masyarakat Desa Kludan RT 01 RW 02 Kecamatan Tanggulangin, Kabupaten Sidoarjo, Provinsi Jawa Timur sebagai korban lumpur lapindo terhadap pemberitaan Aburizal Bakrie yang dicalonkan sebagai Presiden Republik Indonesia periode tahun 2014-2019 dalam berita televisi. Metode yang digunakan adalah analisis resepsi untuk menjelaskan penerimaan dan interpretasi informan dengan menggunakan konsep encoding dan decoding dari Stuart Hall..